The Integration of Traditional Balinese Children’s Song Lyrics in Indonesian Learning to Instill Moral Education Of Elementory School Students in Ubud - Parmini, Ni Putu (International Journal of Elementary Education, 2020)
Cultivating moral values for students is a big problem in the education world, especially learning Indonesian. The purpose of this research was to analyze the effect of the integration of traditional Balinese children's song lyrics in Indonesian learning toward the cultivation of moral education for elementary school students in Ubud. This research used a mixed method approach, namely the concurrent embedded model as a research method. The population of this research was all students, parents, teachers, and principals of  SDN 1, SDN 2, SDN 3, SDN 4 and SDN 5 Ubud. The sample used was 70 students, 70 parents, and 5 homeroom teachers who were taken using purposive sampling method. The data collection methods used were observation, interview and questionnaire sheets. The instrument used was non-test instrument in the form of a moral attitude questionnaire. The analysis techniques used were qualitative descriptive statistical and quantitative with pair sample t-test. The result of the research shows that the sig. pair sample t-test value is 0,000 < then 0,005. The conclusion of this research is the traditional Balinese song could be integrated in Indonesian learning which is significantly effected towards moral attitude of elementary students in Ubud. The implication of this research is able to instill the important character values for students’ life